Inter-island movements of two barbary falcon (Falco peregrinus pelegrinoides) juveniles in the Canary Islands - Rodríguez, Beneharo; Bécares, Juan; Lorenzo, Juan A.; Rodríguez, Airam (Journal of Raptor Research, 2018)
We studied the post-fledging movement of two sibling (male and female) juvenile Barbary Falcons (Falco peregrinus pelegrinoides) hatched in Lanzarote (Canary Islands) in 2011 using satellite tracking. Birds were tracked from fledging in May to the end of November, when the signals of both transmitters were lost. During the first 45 d following fledging, both birds behaved similarly and made some flights <70 km away from their nest, on the island where they hatched. However, after the dependence period, we found differences between the individuals. The female made several inter-island movements among the islands of the central archipelago (Gran Canaria, Tenerife and La Gomera) and returned to Lanzarote in October. In contrast, the male stayed close to his natal nest (<100 km) until the end of October, when he was detected in the middle of the Atlantic Ocean >3000 km from the nest, probably using a ship as a perch. Because Barbary Falcon populations of the Canary Islands are listed as >threatened> due to anthropogenic threats (e.g. collisions with human-made structures, illegal shooting, nest-robbing; and hybridization with escaped falconry falcons) and little is known about their post-fledging dispersal movements, more studies of such life-history characteristics, using ringing and remote sensing, are urgently needed to develop management actions for their conservation.